Using image analysis in the study of multiphase gas absorption - Mena, P. C. (2005)
For the air–water–calcium alginate beads system, the effect of the presence of solids on the mass transfer characteristics in a bubble column was experimentally studied. Volumetric liquid side mass transfer coefficient, kLa, specific interfacial area, a, and hence liquid side mass transfer coefficient, kL, were determined under different solid concentrations (0, 5, and 10 vol%), superficial gas velocities (up to 0.27 cm/s) and solid sizes (1.2 and 2.1mm diameter). The bubble characteristics, namely the interfacial area, were obtained using an image analysis technique. This technique proved to be a suitable and practical method to characterize mass transfer phenomena in bubble columns for the range of operating conditions used. The solids affect negatively kLa, decreasing both a and kL, the effect being more pronounced for the smaller particles. For these particles the variation of kLa is due to the variation of its two components, while for larger particles kLa variation is due, essentially, to changes in kL as no significant differences in a were observed.